Our experience with methyl alcohol poisoning at SLBSGMCH Mandi at Nerchowk - Kumar, Nitesh; Bhawani, Rajesh Kumar; Himral, Pratibha; Lal, Roshan; Dheer, Santosh (International Journal of Research in Medical Sciences, 2022)
Methyl alcohol poisoning is an extremely hazardous poisoning commonly occurs via oral ingestion of illicit or adulterated liquors or as ethanol substitution. Toxicity results in gastrointestinal manifestations, metabolic acidosis, neurologic squeal and even death. Rapid recognition, early and aggressive management have been emphasized to prevent hazardous outcome. We hereby present a case series of 16 cases who presented to our hospital as methyl alcohol poisoning. Demographic, clinical and biochemical data were collected retrospectively from the hospital record section of the tertiary care hospital in the state of Himachal Pradesh. Out of 16 patients admitted, 12 patients had metabolic acidosis and treated with sodium bicarbonate. Four patients underwent hemodialysis for the improvement of symptoms. Five patients with severe metabolic acidosis, hypotension and altered sensorium did not be recover and succumbed.